Mental Health as a Moderating Variable of the Effect of Work Performance Assessment on Employee Performance of Health Workers in East Java - Septin Maisharah (Jurnal Teknologi dan Manajemen Industri Terapan, 2022)
This study investigates the influence of work performance assessment on employee performance, with mental health as a moderating variable. Employing a quantitative explanatory approach, data were collected from 300 health workers and analyzed using SmartPLS 4.0. The findings demonstrate that work performance assessment positively and significantly affects employee performance (p = 0.014). Furthermore, mental health strengthens this relationship, acting as a significant moderating factor (p < 0.001). These results suggest that systematic performance evaluation enhances employee enthusiasm, motivation, and output and highlights the critical role of mental health in optimizing performance outcomes. The study confirms both proposed hypotheses and emphasizes the importance of integrating psychological well-being into human resource management strategies to sustain employee effectiveness and organizational success.